SOCIAL INJUSTICE IN NEIL BURGER’S MOVIE “DIVERGENT” - Meibrianti, Yefuneli; Iskandar, Iskandar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Language is the intelligence to comprehend and produce sign, gesture, posture, written and spoken words that send a certain meaning. Language can bring order to human life and builds social interaction which helps people to express their feelings and thoughts from a person to others. This study uses movies as the object to take the data. Movie is one of the visual aids that can be used to entertain and share the moral value of the story. This study aims to determine the kinds and the cause of social injustices that happen in Neil Burger’s movie “Divergent”. The movie talks about the life of society in the city that is controlled by the government and strong factions. The story begins when a young woman joins the games to know where her personality belongs. The writer will use qualitative research because this study aims to identify the phenomena that is happening in the movie. Moreover, a descriptive method is used because the research describes the characteristics of a particular society or phenomena. The findings in this study take from the dialogues, acts and by seeing the societies’ character. The result of this study shows that there are two kinds of social injustice in the movie. First is stratification among 5 factions, between capitalist faction which is included in parties of a status types and proletary factions which is included in authority types. And the second is discrimination. There are two types discrimination including in this study, social competition and consensual discrimination. Moreover, values and relationships are the causes of the social conflict happening in this study.